Adaptive Strategies of Rural Communities in Nepal to Climate Change Impacts - Gautam, Rajesh Joshi (Spectrum of Humanities and Social Sciences, 2025)
Rural communities in Nepal are increasingly vulnerable to the impacts of climate change, particularly in agriculture-dependent regions like Surkhet District. This study investigates the adaptation strategies employed by these communities to cope with climate variability and associated risks. Findings reveal that households rely on a mix of traditional practices and modern techniques, including crop diversification, water-efficient irrigation, and community-led resource management. The study underscores the critical role of financial, social, and natural capital in shaping adaptive capacity, aligning with the Sustainable Livelihood Framework (SLF) and Community-Based Adaptation (CBA) approaches. Financial capital enables investment in advanced agricultural technologies, while social capital strengthens community resilience through collective action and shared resource governance. Despite these efforts, limited financial support and inadequate institutional backing hinder widespread adaptation, particularly for marginalized communities. This study emphasizes the importance of inclusive climate adaptation policies, enhanced institutional support, and improved financial and technological access to strengthen rural resilience. The insights presented offer valuable guidance for policymakers, development organizations, and local stakeholders in designing sustainable adaptation strategies that address the unique vulnerabilities of Nepal’s rural communities.